One-day point prevalence of emerging bacterial pathogens in a nationwide sample of 62 German hospitals in 2012 and comparison with the results of the one-day point prevalence of 2010 - Wegner, Christian; Hübner, Nils-Olaf; Gleich, Sabine; Thalmaier, Ulrike; Krüger, Colin M.; Kramer, Axel (German Medical Science GMS Publishing House, 2013)
[english] Background: Antibiotic resistance of bacterial pathogens is an emerging problem worldwide. To combat multidrug resistant organisms (MRDOs) networks of care providers have been established in all states in Germany. The HICARE-network, a project to combat MRDOs, founded by the Federal Ministry of Education and Research, has published data from 2010 of a voluntary, German-wide, multicenter point-prevalence survey in 2011 conducted in collaboration with the German Society of Hospital Hygiene. The aim of the present survey was the re-evaluation of the situation in 2012.Method: The survey was conducted as a voluntary, anonymous, point-prevalence in May 2012 using routine data of microbiological diagnostics of the hospitals. As in the former survey of 2010 it was differentiated between primary, secondary and tertiary care hospitals and only data from intensive care units, surgical and medical wards were collected. Based on the survey form used in 2010, an updated version was used including more pathogens and corrected issues observed in the former survey. Methicillin-resistant (MRSA) (total as well as separated in hospital-acquired (HA), community-acquired (CA) and lifestock-associated (LA) MRSA), vancomycin resistant (VRSA/GRSA), vancomycin resistant resp. (VR-resp. VR-), extended-spectrum-beta-lactamase-building (ESBL) (ESBL-EC) and (ESBL-KP), multiresistant spp. (MAB), multiresistant spp. (MRP), carbapenemase-producing Enterobacteriaceae (CRE) as well as (CD) infections and severe infections requiring ICU-treatment were included in the survey along with additional data on screening strategy, the equipment with infection control staff and possible confounders.Results: Out of 1,550 hospitals asked to participate, 62 returned data (4%). Data from 56 hospitals including primary (26), secondary (20) and tertiary (10) care hospitals were analyzable (3.6%). The most frequently reported organisms were MRSA 1.53% [CI95: 1.32-1.75], followed by CDAD 1.30% [CI95: 1.11-1.50], ESBL-EC 0.97% [CI95: 0.80-1.14], and ESBL-KP 0.27% [CI95: 0.18-0.36], regardless of the level of care. Prevalence of MRDOs depended on the level of care and on the type of ward, as expected. Overall prevalence was highest on intensive care wards, and prevalences were remarkably high on medical wards compared to surgical wards. All tertiary care providers employed their own infection control nurse, while only ~70% of the secondary and primary care hospitals did. Surprisingly, in two of the ten participating tertiary care providers neither an internal nor an external infection control doctor was available.Discussion: With more than 13,000 patients in 56 hospitals distributed all over Germany, the survey included more than three times as many patients as the first survey and therefore not only adds valuable information about the epidemiology of emerging nosocomial pathogens, but also helps to raise awareness of the problem of antibacterial resistance in Germany. The prevalences reported seem to be comparable to the results of the former survey and of other surveys published. Some hospitals reported to have no infection control personnel available at all. This statement is in line with another survey published in this issue.